Radiation mutagenesis of microbial biofertilizer for functionalities improvement in cucumber and green mustard - Phua, Choo Kwai Hoe (2019)
Gamma irradiation has been utilised to induce mutagenesis in microorganisms to enhance enzyme production in the fermentation industry. However, radiation mutagenesis of microorganisms to induce multifunctional activities, especially in the biofertilizer industry, has yet to be reported in Malaysia. Eight biofertilizer bacteria, which were isolated from compost, soil, and plants, were subjected to gamma irradiation from a gamma cell at Malaysian Nuclear Agency (Nuclear Malaysia) to improve their plant growth promoting activities, such as N2 fixation, phosphate solubilisation, potassium solubilisation and growth hormone production. Isolates were identified as Acinetobacter calcoaceticus (M100), A. baumannii (AP1), Klebsiella pneumonia (AP2), Enterobacter bacterium (AP3), Pseudomonas putida (C2, V15 and M99), and Pantoea stewartii (V3) by using 16S rRNA method. These isolates were gamma irradiated at doses of 50–400 grey (Gy). Survival curves revealed that bacterial levels (log number of cfu/mL) decreased when gamma irradiation dose was increased. LD50 of the isolates ranged from 400 Gy to 500 Gy. Among the variants, A. calcoaceticus (M100/200) and A. baumannii (AP1/200) irradiated after being given a dose of 200 Gy of gamma irradiation exhibited an improvement in N2 fixation, phosphate solubilisation, and potassium solubilisation. There was no N2 fixation nif gene amplified in A. baumannii (AP1) and A. calcoaceticus (M100). Only phosphate solubilisation pqq genes were amplified by primer pqq7. BLAST results showed only minor changes of the wild type and mutant sequences. Gamma irradiation did not cause major changes of these pqq genes. There could be other pqq genes or molecular changes may occur after gamma irradiation. A. calcoaceticus (M100) and its mutant, M100/200, were tested in greenhouse by using a complete randomised design (CRD) experimental design and field experiment by using complete randomised block design (CRBD) experimental design on cucumber. The mutant enhanced 47.28 % of fresh and 52.63 % of dry weight of five week old cucumber seedlings in the greenhouse experiment and 6.38 % of yields in the field experiment as compared with wild type. Nitrogen and phosphorus are important plant nutrients. The effects of gamma irradiated A. calcoaceticus on the uptake of N and P of green mustard (Brassica chinensis) were investigated in a greenhouse experiment by using complete randomised design (CRD) experimental design. N, P and K contents, as well as pH, were determined using the soil nutrient analyser. Two-week-old seedlings were treated with biofertilizer (mutant or wild type) with either N (urea) or P (phosphate rock) source alone or in combination. Crops were harvested after two months. Fresh and dry weight, height, chlorophyll content, leaf area and total N and P of the crops were determined. Treatment T8 (Mutant M100/200 with N and P source) showed the highest results in plant height (28.75 cm), fresh and dry weights of top part of green mustard (66.33 g and 3.83 g), root length (17.38 cm), fresh and dry weighs of root (4.90 g and 0.97 g), leaf area (938.62 cm2), SPAD reading (40.48) and total chlorophyll (1.97 mg cm-2) in comparison to those of the samples given other treatments in the greenhouse experiment. The highest total N (4.69%) showed in treatment T5 (mutant M100/200 with N source). The highest total P (11.29 mg/L) showed in treatment T7 (M100 with N and P source). Nitrogen input did not enhance growth, whereas phosphorus input and phosphate solubiliser administration increased plant growth indirectly through a better rooting system. In conclusion, Acinetobacter sp. could be improved as multifunctional biofertilizer inoculants through gamma irradiation. Whole genome sequencing for the wild type and mutant may be carried out in determined future investigation of mutagenesis by gamma irradiation.